Evaluation of the efficacy of cevimeline in improving the clinical symptoms of patients with primary Sjögren′s syndrome - WANG Shengming; LI Fangfang; WU Yao; SHI Xinlian; LIU Xin (口腔疾病防治, 2021)
Objective To investigate the clinical efficacy of cevimeline as a pharmacotherapeutic approach to stimulating gland activity in improving the symptoms and signs of primary Sjögren syndrome (pSS). Methods Sixty-three patients diagnosed with pSS who attended the Affiliated Huai'an Hospital of Xuzhou Medical University from January 2018 to September 2019 were included in this trial. They were randomly assigned to the therapeutic group and control group. All patients were recalled at baseline and after 2 weeks, 3 months and 6 months. Measurement of salivary and lacrimal flow as well as evaluation of subjective symptoms was performed at the follow-up. Results Fifty-eight patients completed the trial and were included in the statistical analysis. There was a significant difference between the two groups in the measurement of salivary and lacrimal flow at the second week and third month (P < 0.05). Improvement in subjective symptoms of oral, ocular and gland was detected at the third month (P < 0.05). At the sixth month, compared with the control group, only the salivary gland symptom score of the treatment group was statistically significant (P < 0.05). Conclusion Cevimeline has good specificity and safety and can increase salivary and lacrimal flow and improve subjective symptoms of pSS in a short time.